LAYANAN BIMBINGAN KLASIKAL DENGAN TEKNIK ROLE PLAYING DALAM MENINGKATKAN KECERDASAN EMOSI SISWA KELAS XI 5 SMAN 4 JEMBER - Sherly Rahmadani Izza; Alfian Damayanti; Retno Tri Hariastuti; Sobi Mardiyas (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Adolescence can be considered the peak of emotionality. Many teenagers are unable to understand and manage emotions well. Based on the results of AKPD Class XI 5 at SMA Negeri 4 Jember shows that the highest problem in the personal field is not being able to understand and manage emotions properly. So this study aims to improve emotional intelligence through classical guidance using role playing techniques. The subjects of this study were grade XI 5 students of SMA Negeri 4 Jember with a total of 36 students. The type of research used is classroom action research, guidance and counseling or can be called (PTBK).The research method uses quantitative methods. Data collection in this study used a Likert scale which was then analyzed using the SPSS application version 29.00 using the paired sample test formula. The results of this study show that the value in the one-sided table is 0.001. While the value in the two-sided table is 0.001 where the sig value is <0.05, which means there is a significant difference from the pre-test and post-test results. So it can be concluded that classical guidance with role playing techniques can improve the emotional intelligence of students in grade XI 5 SMA Negeri 4 Jember.